Improving the University Digital Infrastructure Management System: Practice of Social Network Analysis - A. A. Azarov; E. V. Brodovskaya; V. A. Lukushin (Высшее образование в России)
This article presents the results of applied research aimed at developing topical approaches to solving the problem of dysfunctionality of universities’ digital infrastructures in social media. In the context of the large-scale digitalization and networking processes of modern society, higher education institutions are faced with new challenges that threaten their further sustainability and reduce their competitiveness. As a possible solution to this problem, the authors propose a comprehensive study of university network structures in social media and further implementation of actual practices of online profile management and digital communities. By applying the method of social graphs and automated tools for processing open digital data, a universal algorithm for building and interpreting the resulting visual models is defined. The article substantiates the basic problems faced by modern universities in developing their own digital structures, as well as the ways to solve them, aimed at improving digital infrastructure management, establishing effective communication with target groups, consolidating the organizational structure, developing educational and scientific communities, and promoting the university brand. The proposed interactive digital maps have a high practical potential for direct implementation in the management process of the Russian universities.